Rebuilding Agricultural Livelihoods in Post-Conflict Situations: What are the Governance Challenges? The Case of Northern Uganda - Birner, Regina; Cohen, Marc J.; Ilukor, John; Muhumuza, Tony; Schindler, Kati; Mulligan, Sean (International Food Policy Research Institute, 2011)
Most conflicts in the developing world take place in rural areas, displacing large numbers of civilians and disrupting their agricultural livelihoods. Rebuilding agriculture is an important strategy for post-conflict reconstruction. Agriculture is well suited to absorb demobilized combatants, improve food security, and enhance livelihoods. To stimulate agricultural production, post-conflict programs often have to provide agricultural inputs and assets including seeds, tools, and livestock that have been lost during the conflict. However, programs that distribute such inputs are subject to substantial governance challenges, such as leakage of funds and procurement of sub-standard material. Moreover, unlike community infrastructure such as schools or boreholes, agricultural inputs are private goods, and the challenge of capture by better-off households is particularly pronounced. In post-conflict situations, additional challenges arise due to the limited capacity of both government and community-based institutions to implement such programs effectively.